Une analyse de la démultiplication des éthos dit et montré dans le discours du Bourget de François Hollande raconté par Laurent Binet - Alain RABATEL (E-REA)
The present paper examines François Hollande's speech at Bourget in 2012, which marks the opening of his presidential campaign after his victory in the primary election, as it has been staged by Laurent Binet in his narrative of the campaign, Nothing goes as planned. He argues that in several texts – e.g. reports, newspaper articles, etc. – in which the ethos of the enunciators is examined, and not the ethos of the author of the utterance, if the direct speech is in principle the main vector of the ethos, its representation within the narrative affects considerably its co-construction. Under these circumstances it is preferable to speak not only about a presentation of self (ethos 1) through the direct speech, but also of a staged representation of the ethos of the represented utterers, characters or personalities (ethos 2). On this basis, he distinguishes between a shown ethos based on shown enunciations (called shown ethos 1), for which the enunciator of the speech is held responsible, and a shown ethos 2, whenever its manifestations come from the representation of the reported enunciator by a reporting enunciator. The demultiplication of ethos also concerns the said ethos, with a said ethos 1 and a said ethos 2. This dissociation, which underlines the process of co-construction of the ethos, becomes even more complex if the addressees are taken into account, that appropriate this ethos, especially given the fact that the latter is built on shared values. On the one hand, this situation leads to a reexamination of the analysis of the phenomena of commitment because, in the case of the said ethos 2 and shown ethos 2, one could reasonably ask who will be held responsible for it: the reported or the reporting enunciator, or the two of them. On the other hand, this also raises the question of the enunciators’ enunciative responsibilities in the activation of belief processes that form the basis of a shared discursive ethos, privileging the values of the political left (pre-discursive ethos) and minimizing the difficulties of their implementation.